Development of audio-visual media to enhance student comprehension in Islamic education - Sholeh, Muh Ibnu; Mohamed, Mohamed Ramadan Abd Allah; Sokip; 'Azah, Nur; Abror, Sirojuddin (UIN Salatiga, 2024)
This study aims to develop audio-visual media to enhance student understanding in Islamic Education at Madrasah Aliyah Tulungagung. A qualitative approach with a case study design was employed to explore in-depth the processes and experiences associated with the use of this media. The research subjects included Islamic Education teachers, students, the headmaster, and curriculum staff. Data were collected through in-depth interviews, focus group discussions (FGD), participant observations, and documentation. Data analysis involved transcription, coding, categorization, and interpretation. The findings indicate that audiovisual media are effective in assisting students in understanding complex and abstract concepts in Islamic education. This media also boosts student motivation and engagement in learning. However, the use of this media faces challenges such as limited technological facilities and preparation time constraints. The study recommends enhancing support for facilities and providing training for teachers to optimize the use of audio-visual media. With appropriate support, this media has the potential to become an effective tool in improving the quality of Islamic education at Madrasah Aliyah Tulungagung and other madrasahs in Indonesia.